Pendampingan Siswa Belajar Berbasis Belajar Kelompok untuk Meningkatkan Motivasi dan Prestasi Belajar Siswa - Rosyidah, Ummi; Mariana, Erni; Kinasih, Ayang; Qomariyah, Siti; Wardany, Kusuma (Pakis Journal Institute, 2026)
Learning assistance can be done by providing direct explanations of the material so that students can more easily understand the material that has been studied. This community service activity aims to contribute to improving the quality of education in schools, especially related to increasing student motivation and learning achievement through the application of group learning methods. The implementation of learning assistance activities is carried out through learning assistance by applying fun learning methods. This activity aims to increase children's learning motivation, provide explanations of learning materials according to children's interests or materials that are considered difficult, help children in completing school assignments, and provide awards in the form of verbal praise. Assistance in student learning activities can increase their interest and motivation in the learning process. In addition, students become more active in asking questions related to the subject matter. This program helps students develop social awareness of differences in learning speed between individuals. In addition, this activity can also create a more conducive group learning atmosphere.